PENANAMAN TANAMAN JAMBU METE SEBAGAI UPAYA PENGHIJAUAN PADA LAHAN BEKAS PENAMBANGAN TIMAH DI KOTA PANGKAL PINANG - Intan Muning Harjanti; Ratih Widiastuti (Jurnal Pengabdian Vokasi, 2019)
Rangkui Subdistrict is one of the sub-districts located in Pangkal Pinang City, Bangka-Belitung Islands, which has natural wealth in the form of tin, so that this area is famous for tin mining activities. But if a tin has been used up, the land will be left and will cause land damage. So it needs to be done greening on the former tin mining land, by planting cashew by involving the local community. The cultivation of cashew is done as one of the alternative in an effort to improve the environment on ex-tin excavated land, because cashew plants, besides being easily found and planted, they also have the ability to grow on ex-excavated land. The method of planting begins with the selection of good seeds. Before planting, cashew seeds are cultivated first using soil and fertilizer media. After the cashew seedlings are ready to be planted, then the cashew seeds are planted on the former tin excavation land along with soil and fertilizer media that have been integrated with the roots. With the community service activities that provide training in cashew nut cultivation to the community on the former tin excavated land, it is expected to improve the quality of the environment, increase the value of land and improve the economy of the local community. And as an effort to overcome land damage.Keywords: Used tin excavation land, planting, cashew, Rangkui sub-District